CONSUMER’S WILLINGNESS TO PAY FOR ORGANIC RICE: A CONTINGENT VALUATION METHOD SURVEY IN GRESIK - Nur Azizah Azzahra; Noor Rizkiyah; Nisa Hafi Idhoh Fitriana (AGRIBIOS, 2025)
The advancement of science and technology has contributed to an increased consumer awareness regarding the importance of adopting a healthy lifestyle. Currently, trend towards healthier living is developing among consumers, with a growing interest in organic products, such as rice. Despite the rising awareness of healthy food, the high price of organic products often affect the consumers in consuming organic rice. Furthermore, the limited availability of organic rice also plays a significant role in restricting its consumption. This study was conducted to estimate consumers' WTP for organic rice. Through WTP analysis, this research endeavors to measure the extent to which consumers are willing to pay a premium for organic rice. The research was carried out at Superindo in Gresik, involving 51 respondents The research data were analyzed using the CVM. Three types of rice were subjected to WTP analysis: white organic rice, brown organic rice, and black organic rice. The WTP values for white, brown, and black organic rice were obtained as follows: Rp. 38,315.5/kg, Rp. 42,069/kg, and Rp. 49,463/kg, respectively. The differences in consumers' WTP for white, brown, and black organic rice are generally influenced by consumers' perceptions of the health benefits associated with each type of rice.